The Relationship Between Big Five Personality and Social Well-Being of Chinese Residents: The Mediating Effect of Social Support - Yu, Yanghang; Zhao, Yuanyuan; Li, Dongyan; Zhang, Jingqiu; Li, Jiewei (Frontiers in Psychology, 2021)
Previous studies have noted that personality traits are important predictors of well-being, but how Big Five personality influence social well-being is still unknown. This study aims to examine the link between Big Five personality and five dimensions of social well-being in the Chinese cultural context and whether social support can play the mediating effect in the process. This study included 1658 participants from different communities in China, and regression analyses were conducted. Results revealed that Five personality traits were significantly related to overall social well-being; extraversion was significantly related to social integration; agreeableness was positively related to all five dimensions of social well-being; conscientiousness was positively related to social actualization, social coherence, and social contribution; neuroticism was negatively related to social integration, social acceptance, social actualization, and social coherence; openness was positively related to social integration, social acceptance, social coherence, and social contribution. Social support plays mediating roles in the relationships between extraversion/ agreeableness/ conscientiousness/ neuroticism/ openness and social well-being, respectively.